An Analysis Of Non-Government Organisations (NGOs) And Women's Activism In The Politics Of Health Reform In Thailand - Krutmechai, Montawadee; Shuib, Rashidah; Ang , Magdalene Chooi Hwa (2016)
In the early 1990s, Thailand initiated a broad package of reforms in various sectors, including politics, education and health. The health reform brought about direct engagement of government agencies with NGOs and people’s organisations in terms of policy formulation and programme implementation. One of the ‘people’s organisations’ that has gained prominence in offering an alternative health model is the Buddhist Medicine Foundation Thailand (BMFT). Based on a bigger study of BMFT, this paper presents a preliminary analysis of the organisation,using both secondary and primary data; the former were gathered from relevant documents and literature review in a desk-review, while the latter were generated from in-depth interviews of the leader, volunteers and participants.The findings showed the importance of historical reform movements of civil societies, the pluralistic health care system as well as the people-centred ideology of the Tri-Power Model converging to form the socio-historical context of BMFT. Thematic data analysis of the in-depth interviews revealed deep spiritual belief that drives strong voluntarism, with about 80 percent of women involved. BMFT has also shown the capacity to be visible through holistic health activities nationwide, and the capability of being sustainable with its activities contributed mainly by women. BMFT as a people’s organisation has shown to be an important stakeholder in the politics of health reform in Thailand.